Stock Market Integration in South Asia (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
While the topic of stock market integration has been one of the highly researched area in the literature but focus had mostly been on the stock markets of developed economies.  Few have focused on analyzing market integration in South Asian region and no inclusion of Bhutanese stock has been found in the literature in any of the earlier studies. The objective of this paper is to analyze market integration between Bhutanese, Indian and other indices in the region. We also analyzed whether other indices in the region are co-integrated with Indian stock market, as Indian market is more proficient in the region and can be believed to have influences on others. We analyzed all indices in the region on one to one basis (using pairwise co-integration test). We used weekly data from January 2006 to December 2011 period from the stock exchanges of (Bhutan, India, Nepal, Bangladesh, and Pakistan). Applying, Dickey-Fuller method, we tested unit root for each stock indices and used Johansen co-integration approach pairwise to test the long-term relationship between stock indices and multivariate approach to test market integration as a whole. We found that all indices are stationary at I(1) and confirmed no long-term relationship between Bhutanese stock with Indian and other regional stock markets. In fact we find no market integration either on one to one basis or for the south Asian market as a whole. Information on market integration should help market players in managing their investments in capital markets in a sustainable manner.